Analisis Kerusakan Dini Perkerasan Lentur Akibat Beban Berlebih (Overload) pada Ruas Jalan Poros Pinrang – Polewali Mandar - Imam Fadly; Hendro Widarto (Jurnal Rekayasa Teknik, 2022)
The Pinrang - Polewali Mandar road section where the condition is currently experiencing damage at several points caused by the growth of passing vehicles is quite high with excess excess. Based on this incident, the purpose of this study was to determine the proportion of the effect of VDF caused by excess to the effect on the Pinrang - Polewali Mandar axis road. The data used using secondary data in the form of actual vehicle weight data from the Paku weighbridge and LHR. then the proportion of the VDF value is excess by using the Bina Marga method (1990). The time was carried out in May 2022. The results showed that the damage capacity of vehicles crossing the Pinrang – Polewali Mandar axis due to excess overload or VDF overload was 202,497,876 VDF and the actual VDF value in the field was 10.21%, meaning that the excess overload on heavy vehicles can affect the value of VDF. This is because the increase in charge increases, the total of the additions causes an increase in the value of VDF. So it can be the cause of road damage.